EXERCISE TOLERANCE TEST AS A SCREENING TOOL FOR CORONARY ARTERY DISEASE IN ASYMPTOMATIC ADULTS - Wasif Anwar (Army Medical College Rawalpindi, 2020)
Objective: To determine the screening efficacy of exercise tolerance test in the diagnosis of coronary artery disease in asymptomatic physically active adults.